PROVIDING COUNSELING ON CHICKEN LIVER AND MEAT AND MORINGA DIM SUM (DIHATIMO) TO PREVENT ANEMIA IN PREGNANT WOMEN - Indrayani, Triana; Lestari, Risma Fuji; Farida, Ida; Saputra, Dian Dieniawati; Martina, Tina; Nurani, Ratih; Saadah, Siti; Susanti, Susanti; Yulianti, Yuli; Kurniawati, Elis Nia (International Journal of Engagement and Empowerment (IJE2), 2024)
The prevalence of anemia among pregnant women in Garut is alarmingly high, reaching 6669 individuals. A survey carried out at the TPMB Hj. Husnul Khotimah area revealed that 3 out of 7 pregnant women suffer from anemia. This escalating prevalence underscores the necessity of identifying the causative factors associated with anemia. Anemia during pregnancy poses significant risks to both the mother and the fetus. Despite numerous governmental initiatives to prevent anaemia, its prevalence remains stubbornly high. Additional strategies and channels are imperative to curb this trend. This community service initiative aimed to enhance pregnant women's understanding of anaemia, encompassing its aetiology, consequences, and preventive measures. Twenty-five anaemic pregnant women participated in the activity, encompassing data collection, educational interventions, and comprehensive evaluation of field activities. Evaluation methods included interactive discussions and question-and-answer sessions. The execution of this community service activity proceeded according to plan, with positive outcomes. Following counselling on anemia, 88% of participants were able to explain the concept of anemia during pregnancy, 72% were able to explain its aetiology and consequences, 76% were able to identify associated risk factors, 76% were able to recognize signs and symptoms, and 84% were able to explain methods for treatment and prevention. We advocate for pregnant women to prevent anaemia by incorporating iron-rich foods into their diets and adopting the DIHATIMO innovation to increase haemoglobin levels